Dimensions of anxiety and depression and neurophysiological indicators of error‐monitoring: Relationship with delta and theta oscillatory power and error‐related negativity amplitude. (15th May 2020) - Muir, Alexandra M.; Hedges‐Muncy, Ariana; Clawson, Ann; Carbine, Kaylie A.; Larson, Michael J.
Abstract: Error‐monitoring processes may be affected by transdiagnostic dimensions of psychopathology symptoms including trait anxiety, worry, and severity of depressive symptoms. We tested the relationship between continuous measures of anxiety and depressive symptomology and neural correlates of error‐monitoring as measured by time‐frequency domain delta and theta oscillatory power and time‐domain error‐related negativity (ERN) amplitude extracted from the electroencephalogram (EEG). Secondary analyses tested for diagnostic group differences in error‐related neural responses in individuals with generalized anxiety disorder (GAD), major depressive disorder (MDD), and comorbid psychiatric disorders. About 178 participants (104 female, M[SD]age  = 21.7[4.6]) with a wide range of psychopathology symptoms completed a modified version of the Eriksen flanker task and symptom questionnaires. Residualized difference values between correct and error trials for delta/theta power and error/correct ERN amplitude were used as dependent variables. Linear regression analyses adjusted for age, sex, and task accuracy showed nonsignificant associations of symptom dimension measures with error‐related residualized delta/theta power or residualized ERN amplitude. Subset analyses on those with confirmed psychopathology diagnoses also did not predict residualized error‐related delta/theta power nor residualized ERN amplitude ( n GAD  = 14, n MDD  = 28, n Comorbid  = 19, n Control  = 85). Taken in the context of the previous literature, results suggest a heterogeneous relationship between depressive and anxiety symptom dimensions and neurophysiological indices of error‐monitoring. Abstract : In line with the RDoC framework, we tested the relationship between anxiety and depressive symptom dimensions and the neural indices of error‐processing (delta and theta power, error‐related negativity ERP amplitude) in 178 participants with a range of pathology symptoms. A non‐significant relationship emerged between neural and symptom measures suggesting that anxiety and depressive symptomology have a nuanced relationship with error‐monitoring in a large sample across a range of anxiety and depression symptoms.